ANALISIS PENGARUH REWARD, EFIKASI DIRI TERHADAP KINERJA DENGAN TARGETING SEBAGAI VARIABEL INTERVENING PADA BALAI BESAR KARANTINA PERTANIAN SURABAYA - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
This study aims to determine the effect of reward and self-eficacy on employee performance of the Surabaya Agricultural Quarantine Center which is mediated by targeting employee. From the results of the tests conducted, it shows that reward has a positive and significant effect on the performance of the Surabaya Agricultural Quarantine Center employees. Self-efficacy has a positive and significant effect on the performance of the Surabaya Agricultural Quarantine Center's employees. Targeting has a negative and significant effect on the performance of the Surabaya Agricultural Quarantine Center's employees. Reward has a negative and insignificant effect on targeting employees of the Surabaya Agricultural Quarantine Center. Self-efficacy has a positive and significant effect on targeting employees of the Surabaya Agricultural Quarantine Center. Rewards can mediate the performance of Surabaya Agricultural Quarantine Center employees. Self-efficacy cannot mediate the performance of Surabaya Agricultural Quarantine Center employees.